Legal advice and care-effective use of care and case management: limits, risks and need for change (funded by the innovation Fund of the Federal Joint Committee (G-BA) according to §§ 92a and 92b of the fifth book of the German social code (SGB V). Funding code 01NVF17029 (RubiN) regional uninterrupted in the network) - Thomas Ruppel; Max Georg Hügel; Simone Gloystein; Neeltje van den Berg (BMC, 2022)
Abstract Introduction An important dimension of care and case managers is to support geriatric patients in obtaining social services in medical, nursing, therapeutic and social fields. To this, they advise and represent their patients. Methods The documentation of patient contacts with case managers of a network of physicians was evaluated. In particular, activities involving legal advice were analysed in detail, compared with the current legal situation in Germany and evaluated. In addition, qualitative expert interviews were conducted. The content and the legal requirements of legal services law were determined by applying legal interpretation methods (esp. wording, telos, systematics). The results of the evaluation of the documentation were compared with legal requirements. Results Care and case management touches activities in some fields of action without having a legal basis in legal services law. This leads to the fact that these services may not be provided and to - uninsured and uninsurable - liability risks. Discussion With the introduction of care and case management into standard care, both social law and the Legal Services Act must be adapted to enable the legally compliant use of care and case managers. Otherwise, certain services that are useful for the care of patients may not be provided.